2008
DOI: 10.1177/0018726708096636
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being `Indian': Identity centrality and work outcomes in an off-shored call center in India

Abstract: Existing studies of identity dynamics have shown that employees embody multiple social identities, and have multiple foci of identifications at work that shape their attitudes and behaviors. However, limited research has examined these frameworks in the new, emerging contexts of global workplaces. In this article, we focus on one such significant example of contemporary globalization: transnational service work in the international call center industry in India. Our findings indicate that national identity cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 69 publications
0
70
0
Order By: Relevance
“…Once there she becomes 'Carol' and calls various people in the United Kingdom and the United States, to remind them to pay their pending credit card bills in a scene and an identity game repeated in call centres across the 'developing world' (for related commentary see, for instance, Das et al, 2008;Ng and Mitter, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Once there she becomes 'Carol' and calls various people in the United Kingdom and the United States, to remind them to pay their pending credit card bills in a scene and an identity game repeated in call centres across the 'developing world' (for related commentary see, for instance, Das et al, 2008;Ng and Mitter, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Korczynski (2003) has referred to groups of employees forming supportive emotional relationships as 'communities of coping'. Other scholars have noted that emotional labour itself is culturally specific (Das et al, 2008), and different cultures draw the line between genuine and artificial emotional performances very differently (e.g. Bozionelos and Kiamou, 2008).…”
Section: Social Constructionist and Psychoanalytic Approaches To Emotionmentioning
confidence: 99%
“…Consistent with the findings of other studies, this study also found that identification and identity strength negatively influenced turnover intentions; the influence on different levels of organizational hierarchy varied, however. Relatedly, Das, Dharwadkar, & Brandes (2008) investigated the impact of various identities and organizational identification on turnover and performance in an "international/globalized" business context. They found that when the workers of an international call-center have high national identity centrality, it resulted in higher turnover intentions.…”
Section: The Consequences Of Identity At the Individual Levelmentioning
confidence: 99%
“…In the literature review section, I provided a detailed account of how identities in general have bearings on intentionality, ranging from cooperative intentions (Boezeman & Ellemers, 2007) to turnover intentions to withdrawal intentions (Das et al, 2008).…”
Section: Entrepreneurial Identity and Entrepreneurial Intentionsmentioning
confidence: 99%
See 1 more Smart Citation